Pelatihan Praktik Penyelenggaraan Jenazah Sebagai Upaya Penguatan Kompetensi Keagamaan Masyarakat Desa Banyuanyara: Training on the Practical Implementation of Funeral Services as an Effort to Strengthen the Religious Competence of the Community of Banyuanyara Village - Mukran H. Usman; Aswar Aswar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
The management of funerals is a collective obligation (fardhu kifayah) that requires understanding and technical skills in accordance with Islamic law. However, the community of Banyuanyara Village still faces limitations in the number of residents competent in the processes of washing, shrouding, and performing funeral prayers for the deceased, so its implementation tends to depend on a few religious leaders. This service activity aims to improve the religious competence and practical skills of the community through funeral management training. The method used is Participatory Action Research (PAR) with the stages of preparation, socialization, implementation, and evaluation. The activity was carried out on February 22, 2026, at Nurul Asfari Mosque involving religious leaders, village government, and the local community. Data collection techniques were carried out through observation, in-depth discussions, and documentation, while data analysis used a triangulation approach. The activity results showed an increase in participants' understanding of funeral fiqh as well as technical skills in washing, shrouding, and performing the funeral prayer. Community participation was quite high and involved various age groups. The challenges encountered included the participants' limited practical experience and the presence of local myths that caused hesitation to get involved. These challenges were addressed through a persuasive approach, step-by-step demonstrations, and intensive mentoring by speakers from Wahdah Islamiyah. This program has proven effective in strengthening the community's religious competence and encouraging residents' independence in carrying out the fardhu kifayah obligations properly and sustainably.